2022
DOI: 10.1108/mhsi-03-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of the “ABCs of Mental Health” in Denmark and the role of mental health-promoting beliefs and actions

Abstract: Purpose The purpose of this paper is to investigate the overall campaign reach and impact of the ABCs of Mental Health in Denmark; a secondary objective is to investigate how mental health-promoting beliefs and actions are associated with good mental health. Design/methodology/approach A questionnaire was administered to two representative cross-sectional samples of the Danish population (1,508 respondents in 2019; 1,507 respondents in 2021) via an online survey. The data were subsequently pooled together in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The results showed that those who engaged in the identified adaptive actions at least half of the days of the week reported lower symptoms of depression and anxiety, and conversely, increased satisfaction with life. The five domains of actions captured by the TYDQ-21 shared some overlap with the five domains identified by Santini et al [ 9 ], including cognitive actions, health behaviours/routines, and social interactions.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The results showed that those who engaged in the identified adaptive actions at least half of the days of the week reported lower symptoms of depression and anxiety, and conversely, increased satisfaction with life. The five domains of actions captured by the TYDQ-21 shared some overlap with the five domains identified by Santini et al [ 9 ], including cognitive actions, health behaviours/routines, and social interactions.…”
Section: Introductionmentioning
confidence: 75%
“…In a recent Danish study, over 3000 respondents reported the daily actions they took to enhance their mental health. A vast range of actions were reported, from which five main themes emerged: positive mindset (e.g., ‘be optimistic’), health behaviours (e.g., ‘exercise daily’), social relationships (e.g., ‘have a social network’), relaxation (e.g., ‘remember to relax’), and use of the brain (e.g., ‘solve tasks’) [ 9 ]. Actively doing something to improve mental health was associated with greater self-reported mental wellbeing in the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadening a population’s knowledge-base around positive mental health is a key factor in mental health promotion and a cornerstone of the Act-Belong-Commit (ABC) approach to mental health promotion (Donovan et al , 2006). A study published after the time period covered by our search, found the ABC model to increase respondents knowledge about what they can do to enhance their mental health, which was independently associated with a higher level of mental well-being (Santini et al , 2022). The need for mental health interventions to build on accurate and culturally appropriate conceptualisations was highlighted in a recent paper by Haymovitz et al , who explored how mental health was conceptualised in 25 participants of diverse American racial and ethnic groups (Haymovitz et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The campaign originated in Western Australia, where it is directed by Mentally Healthy WA (MHWA) at Curtin University, and is implemented through partnerships with health services, local governments, state government departments, workplaces, community organisations, and local clubs [ 23 ]. The campaign constructs appear to be universal and have been adopted and articulated in a local context in a number of countries around the globe, particularly in Scandinavian countries [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%